2004
DOI: 10.1063/1.1834993
|View full text |Cite
|
Sign up to set email alerts
|

CdSe self-assembled quantum dots with ZnCdMgSe barriers emitting throughout the visible spectrum

Abstract: Self-assembled quantum dots of CdSe with ZnCdMgSe barriers have been grown by molecular beam epitaxy on InP substrates. The optical and microstructural properties were investigated using photoluminescence (PL) and atomic force microscopy (AFM) measurements. Control and reproducibility of the quantum dot (QD) size leading to light emission throughout the entire visible spectrum range has been obtained by varying the CdSe deposition time. Longer CdSe deposition times result in a redshift of the PL peaks as a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…The choice of variable for the x-axis is explained below. A similar observation was already made at lower temperatures (77 K) and a preliminary explanation in terms of enhanced interface effects in the smaller dots was given [3]. Here we show that dot-height fluctuations combined with exciton localization within the base plane of the dots are mainly responsible for this quantum size dependent broadening.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…The choice of variable for the x-axis is explained below. A similar observation was already made at lower temperatures (77 K) and a preliminary explanation in terms of enhanced interface effects in the smaller dots was given [3]. Here we show that dot-height fluctuations combined with exciton localization within the base plane of the dots are mainly responsible for this quantum size dependent broadening.…”
Section: Resultssupporting
confidence: 74%
“…The key development was the introduction of Mg into the barrier material, which allows for a reduction of the lattice mismatch between CdSe and the barrier but retaining their large band-gap difference. In this respect, great progress has been achieved in the degree of control and reproducibility of the growth process of the heterostructures containing Mg [3]. As a result, dots with unimodal size distributions are obtained, in which the average dot size and hence, the emission energy of the CdSe QDs, can be easily adjusted by varying the CdSe deposition time.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Considering all these advantages provided by the magnesium chalcogenides, we recently combined the Zn x Cd y Mg 1ÀxÀy Se barrier with the CdSe binary to fabricate a new QD/barrier material system, CdSe QDs grown on Zn x Cd y Mg 1ÀxÀy Se [30]. There, we demonstrated that changing the CdSe deposition time (t D ), the size and consequently, the photoluminescence (PL) of the CdSe QDs grown on Zn x Cd y Mg 1ÀxÀy Se can be tuned from the blue to red, covering the whole visible spectrum and beyond, offering the promising characteristic of reaching the near-UV when the Zn x Cd y Mg 1ÀxÀy Se bandgap is tuned to UV wavelengths.…”
Section: Introductionmentioning
confidence: 99%
“…The excitation source was a 325 nm He-Cd laser. 18 Figure 1 shows three-dimensional surface photovoltage ͑SPV͒ images of three CdSe/ZnCdMgSe QD samples with different CdSe deposition times: A2027 ͑t D =24 s͒, A2024 ͑t D =13 s͒, and A2023 ͑t D =6 s͒ at room temperature. Photon energy was changing in the direction perpendicular to the scan line from 1.6 to 3.0 eV.…”
mentioning
confidence: 99%